2018
DOI: 10.5056/jnm18049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trimebutine on the Overlap Syndrome Model of Guinea Pigs

Abstract: Background/AimsFunctional dyspepsia (FD) and irritable bowel syndrome (IBS) are common gastrointestinal (GI) disorders and these patients frequently overlap. Trimebutine has been known to be effective in controlling FD co-existing diarrhea-dominant IBS, however its effect on overlap syndrome (OS) patients has not been reported. Therefore, we investigated the effect of trimebutine on the model of OS in guinea pigs.MethodsMale guinea pigs were used to evaluate the effects of trimebutine in corticotropin-releasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…They also found that trimebutine significantly regulated gastrointestinal motility by promoting gastric emptying as well as reducing bowel movements. 62 It is reasonable to speculate the mechanism of trimebutine may be relevant to inhibition of CRF.…”
Section: The Role Of Gastrointestinal Infection In the Pathogenesis Of Irritable Bowel Syndrome Functional Dyspepsia And Overlap Syndromementioning
confidence: 99%
“…They also found that trimebutine significantly regulated gastrointestinal motility by promoting gastric emptying as well as reducing bowel movements. 62 It is reasonable to speculate the mechanism of trimebutine may be relevant to inhibition of CRF.…”
Section: The Role Of Gastrointestinal Infection In the Pathogenesis Of Irritable Bowel Syndrome Functional Dyspepsia And Overlap Syndromementioning
confidence: 99%
“…Regarding preclinical studies, TM was recently shown to be effective at maintaining upper and lower GI motor function in a peripheral CRF overlapping model with guinea pigs [ 33 ]. It is worth noting that apart from GI tract motility disorders, recent data suggest that TM may exert antitumor activities against gut and brain malignancies [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The guinea pig is a good model to study intestinal motility and the enteric nervous system. The models used are similar to what we previously described in rodents, with the use of stress models such as water avoidance and CRH injection ( 269 , 270 ). As a model of altered GI transit, several chemical approaches have been used in guinea pigs such as the gavage with mustard oil and serotonin or the injection of TRH.…”
Section: Non-rodent Modelsmentioning
confidence: 99%